Role of statement of cash flow in forecasting in the global financial crisis 2008: An analytical study for The American Company (Freddie Mac) (Journal of Accounting and Financial Studies ( JAFS ), 2009)
On of the direct causes which led to the global financial crisis 2008 is decrease or collapse in liquidity of large financial institutions which is reflected on investments of a considerable number of institutions and persons.This study aim's through out its three sections to explain the disclosure level of financial institutions which affected by Financial Crisis from liquidity information which explained in the statement of cash flow according to Timeliness and Completeness.The study concluded an important result the company of research sample was disclosure in Timeliness and Completeness from all of accounting information is related in liquidity or that related in result of operations and financial position. The more defectiveness to effected considerable number of investors was doing used relevance analytic procedures for security on its investments.